Isolation ofAeromonas hydrophila in bullfrog tadpoles in the transformation stage - Mouriño, José Luiz Pedreira; Martins, Maurício Laterça; Yamashita, Marcela Maia; Batista, Cleide Rosana Vieira; Pereira, Murilo Anderson (Pesquisa Agropecuaria Brasileira, 2006)
This work aimed to isolate the pathogen responsible for red-leg disease in tadpoles of Rana catesbeiana in their transformation stage. Twenty animals in G4 stage were collected presenting prostration, anorexia, desiccated skin, hemorragic legs and erratic swimming. The bacteria were isolated from samples of heart, liver and legs on tryptone soy agar and blood agar at 25°C for 48 hours. Aeromonas hydrophila was the main responsible for mortality. To evaluate the effect of bacterium, the tadpoles were orally and intraperitoneally infected with 106 CFU mL-1. The appearance of haemorrhagic petechiae on the mouth and internal organs were verified.